Effect of exposure to extremely low frequency magnetic fields on melatonin levels in calves is seasonally dependent - Kolbabová, Tereza; Pascal Malkemper, E; Bartoš, Luděk; Vanderstraeten, Jacques; Turčáni, Marek; Burda, Hynek (Scientific reports, 2015)
The question of health effects of extremely low frequency (50/60 Hz) magnetic fields (ELFMF) has been widely discussed, but the mechanisms of interaction of these fields with biological systems for intensities relevant to human and animal exposure are still under question. The melatonin (MLT) hypothesis suggests that exposure to ELFMF might decrease MLT production thereby promoting cancerogenesis. So far, most studies of MLT secretion under exposure to ELFMF reported negative or inconsistent results. Here, we measured salivary MLT in 1-2 months old cattle calves exposed to 50 Hz-MF in the hundreds of nT-range. We found an inhibitory effect of the ELFMF upon MLT secretion in winter (in accordance with the MLT hypothesis). In contrast, in summer, MLT concentration was increased by ELFMF exposure (contrary to the MLT hypothesis). The inhibitory effect in winter was much stronger than the positive effect in summer. We hypothesize that this season-dependent effect upon MLT synthesis might by mediated by an effect of ELFMF upon the serotonin metabolism and conclude that future tests of ELFMF effects should also measure serotonin levels and consider association with the seasonal effects (photoperiod or temperature) during the exposure.
Keywords: biologické modely; Cattle; Models, Biological; Seasons; mužské pohlaví; ženské pohlaví; sliny; Magnetic Fields; zvířata; Melatonin; Female; skot; roční období; Saliva; melatonin; Male; magnetické pole; Animals